2019
DOI: 10.1111/trf.15626
|View full text |Cite
|
Sign up to set email alerts
|

Blood product transfusion and mortality in neonatal extracorporeal membrane oxygenation

Abstract: BACKGROUND: Neonates receiving extracorporeal membrane oxygenation (ECMO) support are transfused large volumes of red blood cells (RBCs) and platelets (PLTs). Transfusions are often administered in response to specific, but largely unstudied thresholds. The aim of this study is to examine the relationship between RBC and PLT transfusion rates and mortality in neonates receiving ECMO support. STUDY DESIGN AND METHODS:We retrospectively examined outcomes of neonates receiving ECMO support in the neonatal intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 33 publications
1
45
2
Order By: Relevance
“…Platelet transfusion is associated with increased risks of thrombosis and in-hospital mortality in large retrospective studies involving patients with platelet consumptive disorders [27]. Recently published studies suggest that a more restrictive platelet transfusion practice could be appropriate in critically ill neonates [28,29]. In this study, oseltamivir attenuated thrombocytopenia during VA-ECMO and reduced the requirement for platelet transfusion.…”
Section: Discussionmentioning
confidence: 69%
“…Platelet transfusion is associated with increased risks of thrombosis and in-hospital mortality in large retrospective studies involving patients with platelet consumptive disorders [27]. Recently published studies suggest that a more restrictive platelet transfusion practice could be appropriate in critically ill neonates [28,29]. In this study, oseltamivir attenuated thrombocytopenia during VA-ECMO and reduced the requirement for platelet transfusion.…”
Section: Discussionmentioning
confidence: 69%
“…A total of 24.7% of our cases received iNO during severe respiratory failure, although iNO has not been officially approved in extremely preterm neonates [ 41 ]. Because the majority of our neonates were very low birth-weight infants (birth body weight < 1500 g), extracorporeal membrane oxygenation was not available in our institute, and iNO in HFOV with maximal oxygen support may be the final treatment [ 42 , 43 ]. Therefore, a significant proportion of neonates died of cardiopulmonary failure, even though effective antibiotics had been prescribed and their infectious focuses were under control.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study, it reported that platelet transfusion was associated with increase mortality and comorbidities in premature infants with thrombocytopenia [31]. Besides, platelet transfusion rates were associated with hospital mortality (adjusted relative risk per 5ml/kg/d increase: 1.12; 95%CI 1.02-1.23, p=0.02) among neonates receiving extracorporeal membrane oxygenation (ECMO) [32]. In our study, we found nearly the same results among sepsis patients with thrombocytopenia, that platelet transfusion was associated with increased risk of in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%